If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26x + -6 = 5(5x + 2) + -4 Reorder the terms: -6 + 26x = 5(5x + 2) + -4 Reorder the terms: -6 + 26x = 5(2 + 5x) + -4 -6 + 26x = (2 * 5 + 5x * 5) + -4 -6 + 26x = (10 + 25x) + -4 Reorder the terms: -6 + 26x = 10 + -4 + 25x Combine like terms: 10 + -4 = 6 -6 + 26x = 6 + 25x Solving -6 + 26x = 6 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. -6 + 26x + -25x = 6 + 25x + -25x Combine like terms: 26x + -25x = 1x -6 + 1x = 6 + 25x + -25x Combine like terms: 25x + -25x = 0 -6 + 1x = 6 + 0 -6 + 1x = 6 Add '6' to each side of the equation. -6 + 6 + 1x = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = 6 + 6 1x = 6 + 6 Combine like terms: 6 + 6 = 12 1x = 12 Divide each side by '1'. x = 12 Simplifying x = 12
| 12x^3-38x^2+30x= | | Cotx=2/7 | | 2r^2-85=-7 | | ab+2a+2b+4= | | 221-2x=34x+21 | | 3(d+15)-18d=0 | | a^2-ab-5a-5b=0 | | 8x-13=3x+10 | | (x^2)+4x+12=0 | | 4a^7-25a^5= | | 10-5x-2y=1 | | 400a=6000 | | 2x^2-18xy+28y^2= | | y=2cos^4(9-x^2) | | 29-2c=13 | | (x-6)*2+(y+9)*2=6*2 | | -2n-4n+4=-6 | | 8x+24+2x+66=180 | | 5x+106=9x-6 | | 5=3x+6-2x | | (x/-7)-3=11 | | -8r+4(6r+3)=124 | | -6=X-2-2 | | (-9)xm=45 | | 15=-1-3x-x | | 4+35x=28x+16 | | 19+4x+3+y+25=360 | | 3x^2+3bx+3x+3b= | | -7(-4-8x)=84 | | -47-48= | | -91=7(x-7) | | 6=n+6+2n |